Relationship between Lifestyle and Stress Levels in Hypertension Patients - Sari, Diah Lufita; N Sukesi (International Journal of Contemporary Sciences (IJCS), 2024)
Hypertension is a disease that often occurs with increasing age. Hypertension can be influenced by lifestyle factors and stress. This study aims to see the relationship between lifestyle and stress levels in hypertensive patients. The research method used a cross-sectional design with 70 samples in hypertensive patients at KRMT Wongsonegoro Hospital Semarang. Data were collected using a questionnaire. Data analysis used the Spearman rank correlation test to determine how the two variables relate. The results showed a significant relationship between lifestyle and stress levels in hypertensive patients (r = - 0.263, p <0.028). In this study, there were respondents whose unhealthy lifestyles tended to cause blood pressure to rise, causing stress.